2014
DOI: 10.1027/0227-5910/a000266
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Fatality and Demographic Characteristics Associated With Various Suicide Methods

Abstract: The choice of suicide methods and lethality might be influenced by one's demographic characteristics. RESULTS from this study may provide clues for establishing suicide prevention strategies such as restricting access to common lethal suicide methods in the high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Suicide methods were classified using the codes of the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM). Following previous epidemiology research, 20 , 22 , 26 individuals who attempted suicide were classified into two groups based on the lethality of their suicide method. The first, the low-lethal group, consisted of those who attempted suicide through poisoning by solid or liquid substances (E950) or used cutting and piercing instruments (E956).…”
Section: Methodsmentioning
confidence: 99%
“…Suicide methods were classified using the codes of the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM). Following previous epidemiology research, 20 , 22 , 26 individuals who attempted suicide were classified into two groups based on the lethality of their suicide method. The first, the low-lethal group, consisted of those who attempted suicide through poisoning by solid or liquid substances (E950) or used cutting and piercing instruments (E956).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the gender paradox of suicidal behaviour where females report more suicide attempts and males more completed suicides, we suggest that this difference may be influenced by the lethality of the suicide method selected by each group (18). Some authors have even suggested that the choice of the suicide method and lethality is directly influenced by the demographic features of the individual, in particular by gender (12,16,17,20,46).…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with those of previous epidemiologic studies in Taiwan (Kuo et al, 2008, 2012). The demographic characteristics of individuals who choose charcoal-burning as a method of suicide attempt and those using other methods might differ (Lee et al, 2014; Tsai et al, 2011). Suicide by burning charcoal requires a well-organized plan and complicated process (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that older adults (≥50 years) with a repeated suicide attempt were more likely to die by suicide than younger adults (<35 years). Possible explanations are that the elderly might re-attempt suicide by utilizing highly lethal methods, and their vulnerable health conditions were more intolerable to the impact of suicide re-attempts (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation